Sunflower (Helianthus annuus L.) Plants at Various Growth Stages Subjected to Extraction-Comparison of the Antioxidant Activity and Phenolic Profile - Francesco Gai; Magdalena Karamać; Michał A. Janiak; Ryszard Amarowicz; Pier Giorgio Peiretti (MDPI AG, 2020)
The aim of this study was to evaluate the differences in the antioxidant activity and phenolic profile of sunflower (Helianthus annuus L.) extracts obtained from the aerial parts of plants harvested at five growth stages. In vitro assays were used to determine the antioxidant activity, i.e., ABTS•+ and DPPH• scavenging activity, the ferric-reducing antioxidant power (FRAP) and the ability to inhibit β-carotene-linoleic acid emulsion oxidation. Phenolic compounds, such as mono- and dicaffeoylquinic acid isomers and caffeic acid hexose, were identified using the LC-TOF-MS/MS technique. The predominant compound during the growth cycle of the plant was 3,5-di-O-caffeoylquinic acid, whose content was the highest at the mid-flowering stage. The total phenolic content was also the highest in sunflowers at the mid-flowering stage. The main phenolic compound contents were closely correlated with ABTS•+ and DPPH• scavenging activity and FRAP. No significant correlation was found between the total phenolic content and the antioxidant activity in the emulsion system. The highest antiradical activity and FRAP were generally determined in older plants (mid-flowering and late flowering stages). In conclusion, the aerial parts of sunflowers, in particular those harvested at the mid-flowering stage, are a good plant material from which to obtain phenolic compound extracts, albeit mainly of one class (esters of caffeic acid and quinic acid), with high antioxidant activity.